Information security in the South Australian real estate industry. Issue 1 (2014) - Deepa Mani; Kim‐Kwang Raymond Choo; Sameera Mubarak
<x xml:space="preserve"> Abstract </x> Purpose – Opportunities for malicious cyber activities have expanded with the globalisation and advancements in information and communication technology. Such activities will increasingly affect the security of businesses with online presence and/or connected to the internet. Although the real estate sector is a potential attack vector for and target of malicious cyber activities, it is an understudied industry. This paper aims to contribute to a better understanding of the information security threats, awareness, and risk management standards currently employed by the real estate sector in South Australia. Design/methodology/approach – The current study comprises both quantitative and qualitative methodologies, which include 20 survey questionnaires and 20 face‐to‐face interviews conducted in South Australia. Findings – There is a lack of understanding about the true magnitude of malicious cyber activities and its impact on the real estate sector, as illustrated in the findings of 40 real estate organisations in South Australia. The findings and the escalating complexities of the online environment underscore the need for regular ongoing training programs for basic online security (including new cybercrime trends) and the promotion of a culture of information security (e.g. when using smart mobile devices to store and access sensitive data) among staff. Such initiatives will enable staff employed in the (South Australian) real estate sector to maintain the current knowledge of the latest cybercrime activities and the best cyber security protection measures available. Originality/value – This is the first academic study focusing on the real estate organisations in South Australia. The findings will contribute to the evidence on the information security threats faced by the sector as well as in develop sector‐specific information security risk management guidelines. <ack> <x xml:space="preserve"> Acknowledgements </x> The views and opinions expressed in this article are those of the authors alone and not the organisation(s) with whom the authors are or have been associated. The authors would also like to thank the Professor Steven Furnell (Editor, Information Management and Computer Security) and both anonymous reviewers for providing constructive feedback. Despite their invaluable assistance, any errors remaining in this paper are solely attributed to the authors. </ack>